Functional pituitary gonadotroph adenoma in male patients: case report - Ram, Nanik; Sajjad Ali Khan; Das, Bhagwan; Islam, Najmul (Journal of the Pakistan Medical Association, 2022)
Pituitary gonadotroph adenomas are common but very rarely do they secrete biologically active luteinizing hormone (LH) and follicle-stimulating hormone (FSH). There have been case studies reporting high sex hormones (testosterone/estrogen) in the presence of high or normal LH and FSH. Here we report two cases (with their consent) who presented with visual disturbance and headache at a tertiary care hospital (Aga Khan university hospital) Karachi, Pakistan. Brain imaging revealed a pituitary macroadenoma. Further workup was consistent with pituitary gonadotroph adenoma with high FSH (case 1) and normal LH/FSH (case 2) and elevated serum testosterone in both cases. Transsphenoidal resection was performed and the tissue sample histopathology confirmed pituitary adenoma. Postoperatively, improvement in hormonal profile was observed along with a resolution of visual disturbances and headaches. Thus, functional gonadotroph adenoma should be considered in the presence of elevated testosterone/estrogen and normal or elevated follicle-stimulating hormone (FSH)/ luteinizing hormone (LH). —Continue